2015
DOI: 10.1080/03630242.2015.1088119
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and fertility-related stress

Abstract: The investigation of the relationship between alexithymia, the inability to identify and describe feelings and the absence of fantasies, and fertility-related distress is a relatively neglected area of research. The aims of this study were to examine: (1) the prevalence of alexithymia in a sample of infertile women, and (2) the association between alexithymia, coping strategies, and fertility-related stress. This study included 160 infertile women undergoing in vitro fertilization in a public fertility clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
19
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 37 publications
7
19
2
1
Order By: Relevance
“…Furthermore, as in general regards alexithymia scores, the infertile women enrolled in the present study show a TAS-20 mean total score similar to the mean scores obtained by the general Italian population (m = 44.7, SD = 11.3) (Bessi et al 1996). Therefore, these data do not seem to evidence high difficulties in regulating emotion consistently with what has been shown by Gourounti et al (2016) (m = 49.07; SD = 11.9), Lamas et al (2006) showed the strongest effect among the variables included, resulting in a significant variable in influencing the quality of life in all the models utilized. It can also be noted that when the model was tested using the TAS-20 factors scores instead of the TAS-20 total score, the explanatory power of the models greatly increased: for Total FertiQoL from R 2 = 0.29 to R 2 = 0.43; for Total Core FertiQoL from R 2 = 0.25 to R 2 = 0.39; and for Total Treatment FertiQoL from R 2 = 0.24 to R 2 = 0.28.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Furthermore, as in general regards alexithymia scores, the infertile women enrolled in the present study show a TAS-20 mean total score similar to the mean scores obtained by the general Italian population (m = 44.7, SD = 11.3) (Bessi et al 1996). Therefore, these data do not seem to evidence high difficulties in regulating emotion consistently with what has been shown by Gourounti et al (2016) (m = 49.07; SD = 11.9), Lamas et al (2006) showed the strongest effect among the variables included, resulting in a significant variable in influencing the quality of life in all the models utilized. It can also be noted that when the model was tested using the TAS-20 factors scores instead of the TAS-20 total score, the explanatory power of the models greatly increased: for Total FertiQoL from R 2 = 0.29 to R 2 = 0.43; for Total Core FertiQoL from R 2 = 0.25 to R 2 = 0.39; and for Total Treatment FertiQoL from R 2 = 0.24 to R 2 = 0.28.…”
Section: Discussionsupporting
confidence: 70%
“…and this result appears to contrast with Gourounti et al (2016), in which alexithymia was positively associated with infertility duration and age. It can be concluded that in this sample alexithymia is a stable trait and not a state variable or a defence mechanism as hypothesized in previous studies in this field that raised the question of secondary alexithymia as a coping strategy in infertile patients (Gourounti et al, 2016;Lamas et al, 2006;Moreno-Rosset et al, 2011;Shi et al, 2006). Furthermore, as in general regards alexithymia scores, the infertile women enrolled in the present study show a TAS-20 mean total score similar to the mean scores obtained by the general Italian population (m = 44.7, SD = 11.3) (Bessi et al 1996).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this direction alexithymia, literally meaning ‘a lack of words to express emotion’ (Nemiah, Freyberger, & Sifneos, 1976 ), has been conceptualized as an emotional dysregulation disorder, characterized by difficulties in identifying and expressing emotions, in employing fantasy to regulate painful feelings and to find creative solutions to problems as well as in communicating needs to others in order to obtain support (Taylor, 2004 ; Taylor & Bagby, 2013 ). Therefore, alexithymia represents a vulnerability factor and is associated with both physical and mental disorders (Gourounti, Anagnostopoulos, Griva, & Vasmatzis, 2016 ; Grabe et al, 2008 ; Luminet, Bagby & Taylor, 2018 ; Taylor, 2004 ). However, few studies specifically regarding the role of alexithymia in infertility have been conducted to date.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations concerning this specific topic have compared infertile and fertile subjects and have concluded that alexithymia levels are significantly higher among the former (Conrad, Schilling, Langenbuch, Haidl, & Liedtke, 2001 ; Lamas et al, 2006 ; Moreno-Rosset, del Castillo Aparicio, Ramírez-Uclés, & Martín Díaz, 2011 ; Shi, Wu, & Zhu, 2006 ). A small number of studies have explored the relationship between alexithymia and psychopathological dimensions, identifying a positive correlation between alexithymia levels and emotional maladjustment to infertility (Ramírez-Uclés, Castillo-Aparicio, & Moreno- Rosset, 2015 ), anxiety symptomatology (Shi et al, 2006 ), coping strategies and stress (Gourounti et al, 2016 ). Moreover, only one study has identified a significant role of alexithymia as a predictor of infertility-related stress (Dumitru & Turliuc, 2015 ).…”
Section: Introductionmentioning
confidence: 99%